El mal de España: parodia de la visión organicista de la nación en "Tiempo de silencio", de Luis Martín Santos - Gómez, María Asunción (El Colegio de México, 2011)
In Tiempo de silencio (1962), Luis Martín Santos parodies discourse employedby the writers of the Generation of 98 when referring to “el mal de España”.Martín Santos reflects on national identity and on the specific circumstancesof post-Civil War Spain, while highlighting the essentialism, fatalism,and contradictions of the “noventayochistas”. Irony becomes Martín Santos’sweapon of choice by presenting Pedro as the parodic embodiment of the“iron surgeon”, the superior, providential man who was supposed to “rebuild”the homeland, but who instead ends up failing and immersed inthe most absolute nihilism.